Análisis biopsicológico y perfil académico de los estudiantes que ingresan a la Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López", ESPAM MFL, en el periodo abril 2019 – Marzo 2020 - Arauz Barreiro, José Manuel (2020)
The purpose of this research was to know the biopsychological conditions and academic profile of the students who entered ESPAM MFL in the period of April 2019 - March 2020, this was applied to the first and second level of the university. The methodology used in the research was the documentary and the field, through instruments such as the survey and the interview that facilitated the collection of information to be tabulated and analyzed after. The survey was applied to a total of 922 students and the interview to each of the directors of the eight carriers of ESPAM MFL which are; Business Administration, Veterinary Medicine, Computing, Environmental Engineering, Agricultural Engineering, Agrobusiness, Tourism and Public Administration. For the tabulation of the data obtained, we used the statistical software SPSS (Statistical Package for the Social Sciences) version 25, after this the analysis of the results was made taking into account every detail of the biopsychological and academic conditions that affect the learning of an integral professional of the polytechnics, after this, an improvement plan was designed with strategies and actions to mitigate these problems that affect students causing low academic performance and in the worst case, drop-out.